Socio-economic performance of municipalities along the Maputo Development Corridor (MDC): implications for the National Development Plan (NDP) of 2011 - Khoza, Christine; Willemse, Lodene (Department of Urban and Regional Planning, University of the Free State, 2013)
The economic successes of the Maputo Development Corridor (MDC) project demonstrate that corridor development can provide solutions to economic development in landlocked African countries. However, the National Development Plan (NDP) (2011) cites a lack of employment opportunities and under-maintained infrastructure among the inhibitors of economic development, including the area within the MDC, where infrastructure maintenance has, in fact, been praised. This article aims to establish the socio-economic performance of the MDC region between 1996 and 2011, by comparing it to Mpumalanga and the other provinces, and comparing the socioeconomic performance of the six MDC municipalities with each other. Results indicate that the socio-economic performance of the MDC region is consistently better than Mpumalanga and, in certain cases, the region even outperforms the other provinces, thus demonstrating the success of the MDC project. Furthermore, the municipalities that showed stronger economic potential in 1996 (Emalahleni, Steve Tshwete and Mbombela) continued to prosper in 2011 at the expense of the poorer municipalities (Nkomazi, Victor Khayne and Emakhazeni). Policy implications for the NDP (2011) are discussed.

Die ekonomiese suksesse van die Maputo Ontwikkelingskorridor (MOK)-projek dra by tot die idee dat korridorontwikkeling oplossings vir die ekonomiese ontwikkling van omringende Afrikalande kan bied. Nietemin noem die Nasionale Ontwikklingsplan (NOP) (2011) dat die gebrek aan werksgeleenthede en infrastruktuur wat nie onderhou word nie, ondermeer deel van die onderdrukkers van ekonomiese ontwikkeling is, insluitend die area binne die MDC, waar die onderhoud van infrastruktuur geprys was. Die artikel beoog om die sosio-ekonomiese prestasie van die MOK-streek tussen 1996 en 2011 te bepaal deur dit met Mpumalanga en die ander provinsies te vergelyk, en om ’n vergelyking van die ses MOK-munisipaliteite se sosio-ekonomiese prestasie met mekaar te doen. Resultate dui aan dat die sosio-ekonomiese prestasie van die MOK-streek aanhoudend beter as Mpumalanga is, en in sekere gevalle presteer die streek selfs beter as die ander provinsies; dus word die sukses van die MOK-projek gedemonstreer. Bowendien hou die munisipaliteite wat ’n sterker ekonomiese potensiaal in 1996 toon (Emalahleni, Steve Tshwete en Mbombela) aan om in 2011 vooruitgang ten koste van die armer munisipaliteite (Nkomazi, Victor Khayne en Emakhazeni) te toon. Beleidsimplikasies vir die NOP (2011) word bespreek.

Dikatleho tsa moruo projekeng ea Maputo Development Corridor (MDC) di bontsha hore twelopele e phethahetseng e khona ho fana ka di karabo tsa ho tswedisa moruo oa dinaha tsa Afrika tse seng pela leoatle pele. Le ha ho le joalo, National Development Plan (NDP) ea selemo sa 2011 e bontsha ho e na mekhoa ea mesebetsi e mengata, mme le tswelopele ea meruo le ea naha e se teng haholo. Sepheo sa serapa sena ke ho bontsa ho tiia hoa mekhoa ea MDC ea ho phethahatsa tshebeletso tsa bolulo le moruo ho mahareng a selemo sa 1996 le selemo sa 2011. Sena se tla etsoa ka bapisa Mpumalanga le diprofinsi tse ding moo ho bapisonang ditshebeletso tsa bolulo le moruo ka hara masepala e mets’elela ka palo. Diphetho tsa taba tsena di bontsha tshebeletso tsa bolulo le moruo ka hare ho MDC di le betere ho feta tsa Mpumalanga, hape hape ho bonahala ditshebeletso tsa MDC di hlile di le ka hodimo dimo ho feta diprofinsi tse ding; sena se bontsha katleho ea projeke ea MDC. Ho fetisisa, bo masepala ba bontshitseng ho ba le ditshebeletso tsa moruo ka selemo sa 1996, (e leng Emalahleni, Steve Tshwete le Mbombela) ba bontshitse ba tswelapele ho atleha le ka 2011 le ha be lematsa bo masepala ba futsaneileng (joalo ka Nkomazi, Victor Khayne le Emakhazeni) ho atleha ka mokho ba atlehang ka teng. Dipuisano tsa hore na NDP (2011) e amme hakae e teng mona.
Keywords: National Development Plan; Maputo Development Corridor (MDC)